Revisiting Conditional Punishment Jurisdiction in Child Abuse Cases (Study Decision Number X/Pid.Sus-Child/2021/PN.Pwt) - Evan Bonatua Pasaribu, Rodo; Hendriana, Rani; Hapsari Retnaningrum, Dwi; Barkhuizen , Jaco (Jurnal Hukum In Concreto, 2024)
The Criminal Code (KUHP) has regulated alternative sanctions for imprisonment in criminal criminal practices, namely conditional sentences as regulated in Articles 14a to Article 14f of the Criminal Code. One of the sentences related to conditional criminal sentences is Decision Number X/Pid.Sus-Anak/2021/PN.Pwt. This research aims to find out the legal considerations of judges in imposing conditional criminal sanctions on defendants in the Purwokerto District Court Decision Number X/Pid.Sus-Anak/2021/PN Pwt. The approach method used in this research is normative juridical with prescriptive research specifications. The data source used is secondary data by collecting and using literature studies presented in narrative text, and the data analysis method used is normative qualitative. The results of research and discussion show that the judge in deciding Case Number X/Pid.Sus-Anak/2021/PN.Pwt did not consider the theory of retaliation. However, the conditional criminal sentence of 6 (six) months shows that the judge did not consider the fiscal theory, because the defendant has committed criminal acts against 2 (two) other victims.